Ratiometric detection of Cr3+ and Hg2+ by a naphthalimide-rhodamine based fluorescent probe - Mahato, Prasenjit; Saha, Sukdeb; Suresh, E.; Liddo, Rosa Di; Parnigotto, Pier Paolo; Conconi, Maria Teresa; Kesharwani, Manoj K.; Ganguly, Bishwajit; Das, Amitava (Inorganic Chemistry, 2012)
Newly synthesized rhodamine derivatives, L1 and L2, are found to bind specifically to Hg2+ or Cr3+ in presence of large excess of other competing ions with associated changes in their optical and fluorescence spectral behavior. These spectral changes are significant enough in the visible region of the spectrum and thus, allow the visual detection. For L1, the detection limit is even lower than the permissible [Cr3+] or [Hg2+] in drinking water as per standard U.S. EPA norms; while the receptor, L2 could be used as a ratiometric sensor for detection of Cr3+ and Hg2+ based on the resonance energy transfer (RET) process involving the donor naphthalimide and the acceptor Cr3+/Hg2+-bound xanthene fragment. Studies reveal that these two reagents could be used for recognition and sensing of Hg2+/Cr3+. Further, confocal laser microscopic studies confirmed that the reagent L2 could also be used as an imaging probe for detection of uptake of these ions in A431 cells.